Tantalum-containing meso-porous glass fibres for hemostatic applications. (June 2021) - Nagrath, Malvika; Rahimnejad Yazdi, Alireza; Rafferty, Aran; Daly, Dermot; Rahman, Saeed Ur; Gallant, Reid C.; Ni, Heyu; Arany, Praveen R.; Towler, Mark R.
Graphical abstract: Highlights: Biomimetic morphology of the fibres will be beneficial for wound compression. More negative zeta potential will provide a stable matrix for hemostasis. Availability of calcium and tantalum from hemostatic matrices can enhance the coagulation cascade. Abstract: Novel tantalum-containing meso-porous bioactive glass (Ta-MBG) powders, developed via the sol-gel process, have demonstrable hemostatic properties. However, powders can create dust in the operating environment and may be washed away if profuse bleeding occurs. Powders may not adequately compress wound tissue, and in certain circumstances, a thick callus can form, which is challenging to remove. Fibrous forms of MBGs offer advantages over powders for hemostatic applications, yet they appear comparatively under-researched. In this study, Ta-MBG compositions were successfully designed and fabricated into fibrous mats using electrospinning. State-of-the-art imaging techniques were used to investigate the mats. The individual fibres were ∼300 nm in diameter and contained porosity (1−50 nm). There was also micrometre-sized -porosity (1−2 μm) – this constituted the pore space between the matted fibres, unlike the Ta-MBG powders, which comprised of uni-modal channels (pore size: 4 nm) within the particles themselves. Hierarchical micro-nano porosity is known to enhance the activation of coagulation proteins. The surface area and pore volume of the fibrous mats were a maximum of 61 m 2 g −1, 0.23 cm 3 g −1 compared to 374 m 2 g −1, 0.27 cm 3 g −1 for powders. The surface area is an important property facilitating blood fluid sorption and enhancing clotting. The measured zeta potential of the fibres was more highly-negative than that of powder; a highly-negative zeta potential can provide a stable matrix for hemostasis. Overall, the texture of the fibrous mats, the easily-accessible micron-sized pores, the presence of tantalum, the hierarchical porosity, the favourable zeta potential, and the naturally biomimetic architecture are important attributes which make the fibrous mats developed here an attractive alternative for hemostatic applications.